2001
DOI: 10.1080/09553000110062873
|View full text |Cite
|
Sign up to set email alerts
|

Radiation response of apoptosis in C57BL/6N mouse spleen after whole-body irradiation

Abstract: Chronic pre-irradiation at a low dose-rate suppressed Bax-mediated apoptosis. These findings suggest that the radioadaptive response in mouse spleen may be due to a suppression of p53-mediated apoptosis.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
21
1

Year Published

2004
2004
2010
2010

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 57 publications
(24 citation statements)
references
References 13 publications
2
21
1
Order By: Relevance
“…Recently, we reported that the radioadaptive response in mice seems to be induced through the reduction of Trp53-centered apoptosis in hematopoietic stem cells after high-dose exposure (37). Takahashi et al reported that apoptosis of the splenic white pulp (lymphoid organ enclosed by a columnar arterial branch) induced by X irradiation at 3 Gy was suppressed by a chronic low-dose-rate preirradiation (38). In our study, we speculate that the preirradiation could have induced radioresistance in hematopoietic stem cells 9-17 days after exposure, resulting in a swift recovery of the stem cell numbers without stimulated hematopoiesis, allowing in-166 YONEZAWA ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…Recently, we reported that the radioadaptive response in mice seems to be induced through the reduction of Trp53-centered apoptosis in hematopoietic stem cells after high-dose exposure (37). Takahashi et al reported that apoptosis of the splenic white pulp (lymphoid organ enclosed by a columnar arterial branch) induced by X irradiation at 3 Gy was suppressed by a chronic low-dose-rate preirradiation (38). In our study, we speculate that the preirradiation could have induced radioresistance in hematopoietic stem cells 9-17 days after exposure, resulting in a swift recovery of the stem cell numbers without stimulated hematopoiesis, allowing in-166 YONEZAWA ET AL.…”
Section: Discussionmentioning
confidence: 99%
“…16). Our group has reported that p53-dependent apoptosis after exposure to high-dose radiation was also found to be suppressed by chronic irradiation in cultured cells in vitro and in the spleens of mice in vivo (17). In addition, it seems that p53 can control the secretion of certain growthinhibitory factors in response to stress in vitro and in vivo (18).…”
Section: Introductionmentioning
confidence: 98%
“…Of particular interest in the adaptive response is the dose window (i.e., the specific range of doses and/or dose rates) that can serve as a priming irradiation or conditioning irradiation before a challenging irradiation (6)(7)(8). It has been reported that a priming or conditioning low-dose exposure, or an exposure with low dose rates, can induce a p53 tumor suppressor gene-dependent adaptive response in mammalian cells (9)(10)(11)(12)(13). This observation is of interest because the radiation environment in space includes low doses and low dose rates.…”
Section: Introductionmentioning
confidence: 99%